2009
DOI: 10.1051/kmae/2009008
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary trophic network analysis of subalpine Lake Annecy (France) using an Ecopath model

Abstract: Lake Annecy is the second largest natural lake in France, with intensive commercial and recreational fisheries. However, there is limited knowledge of its trophic interaction. A preliminary Ecopath model was fitted to study the trophic interaction in the lake using the available data on most of the ecosystem compartments. Fourteen functional groups were used in the present analysis. Most of the consumers have ecotrophic efficiency from 0.3 to 0.6. The results show that flow from detritus is as important as flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…This capacity of the lake to sustain larval growth might result from the fact that the copepod community is largely supported by terrestrial carbon (Perga et al , 2009). Moreover, the relatively high recreational and commercial fishing pressure on several fish species, including C. lavaretus (Janjua & Gerdeaux, 2009), may also limit food competition.…”
Section: Discussionmentioning
confidence: 99%
“…This capacity of the lake to sustain larval growth might result from the fact that the copepod community is largely supported by terrestrial carbon (Perga et al , 2009). Moreover, the relatively high recreational and commercial fishing pressure on several fish species, including C. lavaretus (Janjua & Gerdeaux, 2009), may also limit food competition.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, the CI and SOI indices were much lower than for Lake Ayame in Ivory Cost (0. 386,0.193), and Lake Annecy in France (0.258, 0.107) and slightly higher than Chinese lakes: Taihu (0.206, 0.042) and Bao'an (0.205, 0.058) (Janjua and Gerdeaux, 2009;Traore et al, 2008). High values of CI and SOI could reflect the high diversity of diet composition while low values indicate a linear food web pattern rather than a web-like structure.…”
Section: Ecosystem Health Assessmentmentioning
confidence: 96%
“…Both studies deal with Lake Annecy and used models implemented inside the Ecopath with Ecosim framework (Christensen et al, 1992). Janjua and Gerdeaux (2009) studied trophic interactions in Lake Annecy using 14 food-web functional groups. The resulting food-web parameters showed that Lake Annecy is a mature and relatively stable ecosystem.…”
Section: D Ecological-only Modelsmentioning
confidence: 99%